Contribution of Academic End-of-Studies Projects to the Startup Initiative Adopted by the Ministry of Higher Education and Scientific Research: The Case of the Valorization of Agri-Food Industry By-Products in Algeria - Saci, Ahmed; Gharbi, Samia (The North African Journal of Food and Nutrition Research, 2025)
In this paper, we present a discussion or a viewpoint regarding the importance and role of academic end-of-studies projects for the Start-up Initiative adopted by the Ministry of Higher Education and Scientific Research to contribute to the valorization of by-products from the agri-food industries in Algeria due to their economic and environmental importance, and considering them as an available and low-cost basis for students wishing to engage in entrepreneurship and create micro-enterprises or start-up enterprises. We also note some specific opinions that could improve this initiative.